Efektywność akademickich klubów sportowych funkcjonujących w szkolnictwie wyższym - Brzezicki, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the article, the efficiency of 29 academic sports clubs in 2017 was measured using the NR-DEA (non-radial-efficiency data envelopment analysis) model. Two empirical models characterizing two different areas of activity of academic sports clubs were used in the study. The first model (M1) focused on club productivity, it includes the number of people practicing in the club and the total numberof points obtained in the Polish Academic Championships. The second model (M2) focused on club activity, it takes into account the number of organized events and participants taking part in the events.The results obtained show that sports clubs of technical universities were more often effective in terms of productivity than in terms of activity. A different situation occurs in university clubs, which were more often effective in terms of the activity of sports events, sporadically in terms of productivity.
Keywords: sports clubs; academic clubs; sport; higher education; academic sports association